Inactivation effect and mechanism of ultrasound combined with ultraviolet treatment on Bacillus cereus spores - Yajin Qi; Xiao Hu; Yi Chen; Ruiling Lv; Tian Ding (Journal of Agriculture and Food Research)
Bacillus cereus is a common foodborne pathogen, and its formation of strongly resistant spores renders the pathogen difficult to eliminate completely using traditional sterilization methods. This study aimed to investigate the inactivation effect of ultrasound combined with ultraviolet treatment on Bacillus cereus spores and the underlying mechanism. The inactivation effect, surface properties, structural changes, heat resistance and germination characteristics, as well as Raman spectroscopy results, were examined. It was found that 20 min of ultrasound combined with ultraviolet treatment resulted in the inactivation of 4.61 log CFU/mL. Structurally, the exosporium and coat were damaged. Moreover, the permeability of the inner membrane increased. Damage to the spores’ structure reduced the heat resistance. Raman spectroscopy indicated that the DNA and proteins were severely damaged.In conclusion, ultrasound combined with ultraviolet treatment demonstrated a synergistic inactivation effect on Bacillus cereus spores by destroying the external structures of the spores, as well as the internal DNA and other substances. This study has preliminarily elucidated the mechanism of ultrasound combined with ultraviolet treatment regarding the inactivation of Bacillus cereus spores, providing a theoretical foundation for its application in food sterilization.